Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

You can ask your own question or look at similar Maths questions.

Step 1. Divide both sides of the equation by 2:

2/2(3x+8)=(-23+9)/2

=> 3x+8=-14/2

=> 3x+8=-7

Step 2. Substract 8 from both sides

3x+8-8=-7-8

=>3x=-15

Step 3. Divide both sides by 3

3x/3=-15/3

=> x=-5

when u multiply 2 in brackets then u obtain 6x+16=-14

6x=-14-16

6x=-30

divide 6 on both sides

x=-5

Expand the brackets and then it becomes a lot easier

6x + 16 = -14

6x = -14 -16

6x = -30

x = -30/6 = -5

6x + 16 = -14

6x = -14 -16

6x = -30

x = -30/6 = -5

6x + 16 = -14

6x = -14 -16

6x = -30

x = -30/6 = -5

-5

Step 1: Simplify both sides of the equation

-23 + 9 = -14

2 (3x + 8) = 6x + 16

Therefore 6x + 16 = -14

Step 2: Collect all the terms of "x" on one side, and all of the numbers on the other. In this case this is done by subtracting 16 from both sides

(6x + 16) - 16 = -14 - 16

-->   6x = -30

Step 3: Further simplify to find the value of x. In this case by dividing both side of the equation by 6

6x/6 = -30/6

--> x = -5

2(3x+8) = -23+9

goes to:

6x + 16 = -23+9 (because you multiply 2 and 3x together to get 6x, and 2 and 8 together to get 16)

This goes to:

6x + 16 = -14 (-23 + 9 is the same as 9 - 23, which equals -14)

This goes to:

6x = -30 (you minus 16 from both sides - you're allowed to do this because it's the same to both sides)

This goes to:

x = -5 (because you divde both sides by 6)

Ta Da! Hope this helps.

2(3x+8) = 23+9

or 6x+16=32

or 6x=16

or x = 16/6=2.67

Hi there,

So this problem requires you to find the value of x. To do this, first add the 9 to the -23. You should get:

2 (3x + 8) = -14

Then, multiply out the bracket - so times everything within the bracket by the 2 on the outside. This will leave you with;

6x + 16 = -14

Now you should take 16 away from both sides of the equation in order to keep it balanced. Hence you will have:

6x = -30

The final step is to divide both sides of the equation by 6, leaving you with:

x = -5

2(3x+8)=-23+9

or, 6x+16=-14

or, 6x=-14-16=-30

or, x=-30/5=-6

Make sure that you work one step at a time, applying the basic rules of algebra at every step. Mark's solution below is an exemplary solution, there are other ways you could do it which would get the same solution.

2(3x + 8)= -23+9

2(3x + 8)= -14

(3x + 8)= -7

3x + 8 =`-7

3x = -15

x= -5